Ethnomathematics and the Hijri Calendar in Grobogan’s Earth Alms Tradition - Auliya, Nanang Nabhar Fakhri; Aulia, Rizky; Ulya, Shofi Nuril (Jurnal Pendidikan Matematika, 2026)
This study investigates ethnomathematical concepts embedded in the Earth Alms tradition in Karangjati Hamlet, Grobogan Regency, and examines their relationship with Islamic values and the Hijri calendar system. The study responds to the limited integration of cultural and religious contexts in mathematics learning, which often causes mathematics to be perceived as abstract and disconnected from students’ daily lives. Using a qualitative ethnographic approach, data were collected through in-depth interviews with traditional leaders, religious leaders, and community members; participatory observations; and documentation studies. Data were analyzed using thematic analysis through coding, categorization, and interpretation processes. The findings reveal that the tradition contains various mathematical concepts, including geometry in the structure of tumpeng and gunungan, social arithmetic in the distribution of agricultural products and community contributions, classification in the arrangement of crops, and pattern concepts in cultural processions. The use of the Hijri calendar and Javanese weton system also reflects mathematical ideas related to cycles, periodicity, and time calculation. In addition, the tradition embodies Islamic values such as gratitude, cooperation, charity, and social responsibility. These findings indicate that local traditions can serve as meaningful contextual mathematics learning resources that integrate cultural and spiritual dimensions. This study contributes to the development of culture-based and religion-based mathematics learning through ethnomathematical perspectives. Penelitian ini mengkaji konsep-konsep etnomatematika yang tertanam dalam tradisi sedekah tanah di Dusun Karangjati, Kabupaten Grobogan, dan meneliti hubungannya dengan nilai-nilai Islam dan sistem kalender Hijriah. Penelitian ini menanggapi terbatasnya integrasi konteks budaya dan agama dalam pembelajaran matematika, yang seringkali menyebabkan matematika dianggap abstrak dan terputus dari kehidupan sehari-hari siswa. Dengan menggunakan pendekatan etnografi kualitatif, data dikumpulkan melalui wawancara mendalam dengan para pemimpin tradisional, pemimpin agama, dan anggota masyarakat, observasi partisipatif, dan studi dokumentasi. Data dianalisis menggunakan analisis tematik melalui proses pengkodean, kategorisasi, dan interpretasi. Temuan menunjukkan bahwa tradisi tersebut mengandung berbagai konsep matematika, termasuk geometri dalam struktur tumpeng dan gunungan, aritmatika sosial dalam distribusi hasil pertanian dan kontribusi masyarakat, klasifikasi dalam pengaturan tanaman, dan konsep pola dalam prosesi budaya. Penggunaan kalender Hijriah dan sistem weton Jawa juga mencerminkan gagasan matematika yang berkaitan dengan siklus, periodisitas, dan perhitungan waktu. Selain itu, tradisi tersebut mewujudkan nilai-nilai Islam seperti rasa syukur, kerja sama, amal, dan tanggung jawab sosial. Temuan ini menunjukkan bahwa tradisi lokal dapat berfungsi sebagai sumber belajar matematika kontekstual yang bermakna dan mengintegrasikan dimensi budaya dan spiritual. Studi ini berkontribusi pada pengembangan pembelajaran matematika berbasis budaya dan agama melalui perspektif etnomatematika.